Analysis of nonlinear parity-time symmetric four-layer Bragg grating - Witoński, Piotr; Mossakowska-Wyszyńska, Agnieszka (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
The one dimensional PT (parity time) symmetric four-layer Bragg grating with gain and loss saturation effects is analyzed taking into account the evolution of the field amplitudes. The investigated structure has modulated real and imaginary parts of refractive index. The functional configurations of the Bragg grating have been considered, showing the behavior of this structure acting as a discrete device and as a component of an integrated circuit. The obtained characteristics illustrate the influence of the saturation effect on the intensity of the output wave at a given intensity of the incident plane wave for different values of gain and loss saturation intensities of the PT structure. The performed analysis shows the bistability of the structure and a strong influence of the incident wave intensity on the properties of light propagation nonreciprocity.
Optica Applicata, Vol. 52, 2022, nr 3, s. 329-344
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; integrated optics; nonlinear optics; Bragg grating; parity time